Inseguridad social y ansiedad en los habitantes de la Cdla. Puertas Negras de la ciudad de Babahoyo - Calero Macías, Melanie Yelitza (2024)
Social insecurity is addressed from various perspectives including quantitative and sociocultural approaches, and in turn, it is addressed from three dimensions; the analysis of perceived risk, the "fear of crime" and the conative dimension that highlights the preventive actions that people choose. Therefore, social insecurity is considered as the existence of a real risk or threat to the health of the population in different contexts, such as urban violence, natural disasters and other community aspects. Although citizen security is the responsibility of the state, it continues to persist in various areas with high levels of violence and crime. In the field of anxiety, a psychodynamic approach is presented that examines intrapsychic activity, a behavioral approach that highlights the importance of consequences in behavior, the three-dimensional approach that considers three independent response systems: cognitive, physiological and motor or behavioral. and a cognitive-behavioral approach proposed by Beck and Clark that differentiates between normal and abnormal anxiety, focusing on the inadequate or exaggerated interpretation of an aversive event as the essence of anxiety. Therefore, a cognitive model of anxiety by Beck and Clark is shown, which includes modes of orientation, activation of the primary mode of threat and secondary elaborative reappraisal. Therefore, the symptoms are described in physiological, cognitive, behavioral and affective aspects, which indicates the great impact of hypermodernity, and this is the main cause of the anxiety that is present in individuals today.